Recent advances in characterization technology for value-added utilization of coal tars. (15th February 2023) - Ma, Zhi-Hao; Li, Sheng; Dong, Xue-Qian; Li, Min; Liu, Guang-Hui; Liu, Zhong-Qiu; Liu, Fang-Jing; Zong, Zhi-Min; Cong, Xing-Shun; Wei, Xian-Yong
Highlights: Non-mass spectrometric characterization methods for coal tar are discussed. Methods for molecular identification of coal tar are elaborated in detail. Properties of coal tar pitch-based carbon material are evaluated. Abstract: Coal tars are by products from coal pyrolysis, carbonization, and gasification, and are raw materials for obtaining value-added chemicals and carbon materials. Molecular characterization and identification of structural information and properties of coal tars are of great significance for effectively utilizing coal tars. This paper mainly elaborated on the sources of coal tars, the compound types in coal tar, the non-mass spectrometric and mass spectrometric characterization of coal tars, and the performance evaluation of coal tar pitch-based carbon materials. We hope that this review will contribute to the enthusiasm for investigating the value-added utilization of coal tars.